Dietary intake with supplementation of vitamin D, vitamin B6, and magnesium on depressive symptoms: a public health perspective - Rohitha Rajasekar; Julia VanderMolen; Katie Barnhart; Nicole Anguilim (Frontiers Media S.A., 2024)
ObjectiveThis study aims to understand the impact of dietary intake through supplementation of vitamins D, B6, and magnesium on elevated depressive symptoms, a mental health illness that is a leading contributor to global disability and a public health concern.MethodsMultiple datasets from the National Health and Nutrition Examination Survey 2017-March 2020 investigated the associations between vitamin D, B6, and magnesium on depression screening scores. A cross-sectional sample of adults over 20 was extracted (n = 9,232). Chi-square tests and logistic regression analyses were used to investigate the associations.ResultsIndividuals with low amounts of vitamin D (p = 0.0481) were more likely to report elevated depressive symptoms relative to those with low amounts of vitamin B6 (p = 0.0225). These results remained significant among those with high magnesium (p = 0.0133) proportionate to high vitamin B6 (p = 0.0225). In the age-adjusted model, a lower intake of vitamin D, vitamin B6, and magnesium showed a relationship with elevated depressive symptoms (Vitamin D: OR = 0.611, 95% CI 0.382-0.980 Vitamin B6: OR = 0.503, 95% CI 0.291-0.867 Magnesium: OR = 0.458, 95% CI 0.277-0.759). The fully adjusted regression model (gender, race/ethnicity, and household food security) showed that a lower intake of vitamin B6 and magnesium correlated with elevated depressive symptoms (Vitamin B6: OR = 0.439, 95% CI 0.260-0.738 Magnesium: OR = 0.465, 95% CI 0.303-0.714).ConclusionPreventive measures could be addressed by identifying the risks of vitamin deficiencies. Further epidemiological research is needed for the individual effects of vitamin supplementation and depression screening scores. Future prospective cohort studies exploring these associations, focusing on daily dietary intake, are needed to validate the direction of causation further and understand the underlying mechanisms.